EFL Student's Experiences with AI Chatbots: A Critical Discourse Analysis - Munir, Bayanuddin; Sulaiman, Umar; Rasyid, Muhammad Nur Akbar; Afiif, Ahmad (Langkawi: Journal of The Association for Arabic and English, 2025)
While existing literature highlights the affective and technical affordances of chatbots, limited attention has been given to their discursive and structural impact on classroom power relations and learner identity. To address this gap, this qualitative study draws upon four theoretical frameworks: Digital Empowerment (Passey, 2014), Communicative Competence (Hymes, 1972), Social Constructivism (Vygotsky, 1978), and Critical Discourse Analysis (van Dijk, 1998). Data were collected through semi-structured interviews with twelve EFL students who regularly engaged with AI chatbots as interactive speaking partners. Employing thematic and discourse analysis, the study identifies three significant findings. 1) Chatbots foster digital autonomy and enhance learner confidence by providing emotional safety, immediate feedback, and opportunities for self-regulated learning; 2) Students acknowledge that chatbot interactions often lack adequate sociolinguistic nuance and contextual sensitivity, limiting their effectiveness in fully authentic communication scenarios; and 3) The integration of chatbots into language practice represents a pedagogical shift that encourages active learner engagement and disrupts traditional teacher-centered classroom authority. Collectively, these findings indicate that chatbots transcend their roles as mere technological tools, actively influencing learners' sociocognitive experiences and identities. This research contributes theoretically by applying Critical Discourse Analysis to AI-mediated learning contexts and practically by guiding educators and chatbot developers toward creating inclusive, empowering, and learner-centered digital tools.